TEORI GENERATIF-TRANSFORMATIF NOAM CHOMSKY DAN RELEVANSINYA DALAM PEMBELAJARAN BAHASA ARAB - Permata, Bagus Adrian (IAIN Kediri, 2015)
Language, as a tool of communication, attracted serious attention from linguists who formulate theories ofÃ‚Â language. Noam ChomskysÃ¢â‚¬â„¢s generative transformative theory, among others, is believed to have put impactsÃ‚Â on the development of linguistics. The theory suggested that language skills are a congenital human potentialÃ‚Â (innate) rather than a nature product. This article examines the relevance of generative transformative theoryÃ‚Â with Arabic learning as a foreigh language. It argued that the theory is reasonably though not fully relevant inthis context. The reason is that Arabic contains universal characteristics as any other languages in the world.Keywords: Teori Bahasa, Generatif-Transformatif, Bahasa Arab sebagai Bahasa Asing